El consumo alimentario: abordaje teórico-crítico en la interfase economía, salud y ambiente (Tema Central) - Izurieta Guevara, Mónica Gioconda (2022)
The purpose of this research is to contribute to the discussion of food consumption using an innovative approach in the transdisciplinary interface of the economy, health, and the environment. To this end, food consumption is explained from a theoretical perspective, in the interpretive framework of the social determination of health. Thus, based on the current dynamics of the corporate food regime, we have identified critical food consumption processes related to the commercialization and harmfulness of diets, the occupation of space for distribution, food advertising, and corporate lobbying towards the state. The relationships of these processes with the health and illness of the bodies and the expressions in the environment are hereby explained. This provides a comprehensive view of food consumption that surpasses the claims of consumer sovereignty and the reductionist approach of nutrition and dietetic sciences; both fields limited until this date to an abstraction of the reality of food at an individual level.